A high concentration of abscisic acid inhibits hypocotyl phototropism in Gossypium arboreum by reducing accumulation and asymmetric distribution of auxin. (18th June 2021) - Zhu, Jin-Dong; Wang, Jing; Guo, Xi-Ning; Shang, Bao-Shuan; Yan, Hong-Ru; Zhang, Xiao; Zhao, Xiang
Abstract : Higher abscisic acid in Gossypium arboreum compromises the accumulation and asymmetric distribution of auxin in hypocotyls in response to light, resulting in weaker phototropism in comparison with G. raimondii. Abstract: Hypocotyl phototropism is mediated by the phototropins and plays a critical role in seedling morphogenesis by optimizing growth orientation. However, the mechanisms by which phototropism influences morphogenesis require additional study, especially for polyploid crops such as cotton. Here, we found that hypocotyl phototropism was weaker in Gossypium arboreum than in G. raimondii (two diploid cotton species), and LC-MS analysis indicated that G. arboreum hypocotyls had a higher content of abscisic acid (ABA) and a lower content of indole-3-acetic acid (IAA) and bioactive gibberellins (GAs). Consistently, the expression of ABA2, AAO3, and GA2OX1 was higher in G. arboreum than in G. raimondii, and that of GA3OX was lower; these changes promoted ABA synthesis and the transformation of active GA to inactive GA. Higher concentrations of ABA inhibited the asymmetric distribution of IAA across the hypocotyl and blocked the phototropic curvature of G. raimondii . Application of IAA or GA3 to the shaded and illuminated sides of the hypocotyl enhanced and inhibited phototropic curvature, respectively, in G. arboreum . The application of IAA, but not GA, to one side of the hypocotyl caused hypocotyl curvature in the dark. These results indicate that the asymmetric distribution of IAA promotes phototropic growth, and the weakened phototropic curvature of G. arboreum may be attributed to its higher ABA concentrations that inhibit the action of auxin, which is regulated by GA signaling.